Етоноконфесійна політика російського царизму в Правобережній Україні (кінець XVIII - початок XX століття). (Zaporizhzhia Historical Review, 2021)
The author examines the ethnoconfessional politics of Russian czarism in Right-bank Ukraine since the end of XVIIIth till the beginning of XXth century.